The impact of an organizational-level mindfulness-based intervention on workplace social capital and psychological safety: A qualitative content analysis - Bonde, Emilie Hasager; Mikkelsen, Eva Gemzøe; Fjorback, Lone Overby; Juul, Lise (Frontiers in Psychology, 2023)
Background: Through the past decades, the mental health of the European population has been continuously declining. Social relations in various spheres of life, including workplace settings, have been shown to impact mental health. Mindfulness-based stress reduction (MBSR) has been found effective in enhancing well-being, and reducing perceived stress, and symptoms of depression and anxiety. Research into mindfulness-based interventions (MBIs) in workplace settings has shown that these interventions may positively affect workplace outcomes, such as interpersonal relations. However, research regarding the organizational impacts of MBIs is still nascent. The objective of this study was to investigate how an organizational-level mindfulness-based intervention (MBI) including a workplace-adapted mindfulness-based stress reduction (MBSR) programme may impact workplace social capital and psychological safety. Methods: Four small and medium-sized private companies were included in this study, representing 368 employees and managers. The intervention consisted of three steps: 1. Mandatory participation in introductory sessions on mental health and mindfulness, 2. Voluntary participation in a 10-week workplace-adapted MBSR programme, and 3. A workshop for selected employee representatives and managers on further implementation of mindfulness. Data was collected using pre and post-intervention focus group interviews. In total, 27 interviews including 76 respondents were conducted. Verbatim transcription was performed. Data was analyzed using deductive content analysis with theoretical frameworks for social capital and psychological safety. Results: The analysis resulted in three main categories: 1. Social capital (1.1. bonding social capital, 1.2. bridging social capital, 1.3. linking social capital), 2. Psychological safety, and 3. Emergent theme: The role of lockdown on the perceived organizational impact of a workplace MBI. The greatest impact was found relating to the bridging social capital, i.e. social capital between departments, and psychological safety among colleagues at the same level of employment. Conclusions: The results indicate that company participation in this organizational-level MBI including a workplace-adapted MBSR programme may positively impact social relations at work, especially the bridging social capital and psychological safety between colleagues at the same level of employment. These results may be have been influenced by lockdowns due to the Covid-19 pandemic.